The Effect Of Audit Tenure, Auditor Switching And Institutional Ownership On Financial Statements Integrity - Dwi Rahmadanti Fitriyana; Shinta Ningtiyas Nazar (Information Technology and Science (ITScience), 2022)
This study was conducted to analyze the effect of audit tenure, auditor switching and institutional ownership on the integrity of financial statements. The research was conducted on property and real estate companies listed on the Indonesia Stock Exchange in 2016-2020. The methodology used is multiple linear regression. The sample selection was carried out using purposive sampling method from secondary data in the form of financial statements and found as many as 44 sample companies with a total of 5 years of observations, so that the total sample in this study was 220 financial statements. Hypothesis testing was carried out using the Eviews series 10 application. Based on the test results, it showed the influence of institutional ownership on the integrity of financial statements, but did not show any influence between audit tenure and auditor switching on the integrity of financial statements. Based on the results of this test, it is also found that there is a joint effect of audit tenure, auditor switching and institutional ownership on the integrity of financial statements